"I Don't Want to Spend My Life under a Toilet Seat": Aspiration, Belonging, and Responsible Masculinities in the Lives of White, Working-Class Boys in a Youth Inclusion Program at the YMCA. Issue 2 (1st December 2019) - Wignall, Ross
Abstract : Working with a cohort of boys aged 14–18 and classed as not in employment, education, or training (NEET) at the Young Men's Christian Association (YMCA) in the UK city of Brighton and Hove, this article follows their progress as they engage with instructors and other pupils at the YMCA, using qualitative modes of inquiry to explore their reactions, feelings, and attitudes. As I demonstrate, their aspirations and sense of emergent manhood is often predicated on new relationships generated in the YMCA spaces rooted in a culture of caring and responsible masculinity founded on implicit Christian values. Through interviews with young men and the people around them, I probe some of the tensions in this process, showing how persistent attachments to places and spaces beyond the YMCA can create feelings of ambivalence and, in some cases, a sense of alienation and marginality even as they begin to feel that they belong.